Penurunan Produktivitas Kerja Terkait Distres Psikologis, Serta Terapi Mandiri Yang Mudah Dan Murah - Suparno (Universitas Brawijaya, Indonesia, 2009)
Distress, in generally followed by psychiatric disorders, it's caused by stressors exposure. Appearance and form of the stressors exposure are met on psychological stressors, physically stressors or mixed stressors. Whereas, still more medicinal practise controversion about psychologically stressors role on holistic health condition. The importance of religion for health can be seen in the definition set forth by the World Health Organization (WHO, 1984), which states that the spiritual aspect is one of the elements of the concept of complete health. From the point of view of mental health, prayer and remembrance of God contain deep psycho-therapeutic elements. This psychoreligious therapy is no less important compared with psychiatric psychotherapy, as it contains spiritual/religious powers which awaken self confidence and optimism (the hope of being cured). These two factors, self confidence and optimism, are two elements essential to curing illness besides medicines and medical treatment administered. Someone who have experienced trauma have difficulty regulating mind-body-spirit functions. Distress, anxiety and depression are outcomes, and its an ongoing process to keep these systems in balance. Modern science and medicine consider human body as merely electro-chemical, electro-mechanical and physical phenomena; human body as the energy system (mind-body-spirit functions).Human energy centers are situated near the key endocrine glands and nerve groups (plexus) that wireless connection to brain and also connection to cosmic universal energy (also called the chakras); while universal cosmic energy (everything is common at atomic level).Developing and applying energy management skills as integration of deep-breathing, meditation, praying and remembrance is vitally important for health maintenance, harmonious relationships, spiritual development, personal transformation and ultimately world peace and a new paradigm.